Infusion Therapy for Correction of Electrolyts in Blood Plasma in Surgery Patients with Rectal Bowel Cancer After Front Resection of Lines of Line - Varivoda Євген; Dzis Богдан; Kondratsky Богдан; Stasyshyn Олександра; Krasivska Валерія; Humeniuk Ольга; Hayduchok Ігор; Reheda Михайло; Tsysnetska Аліна; Varivoda Василь; Dzis Роман; Karpovich Євгенія (Actual Problems of Medicine and Pharmacy, 2022)
In 30 cancer patients with rectal cancer after anterior resection of the rectum, a clinical study of the effect of intravenous infusions of the complex drug Sorbilact multifunctional action on plasma electrolytes in operated patients in the early postoperative period. Studies have shown that intravenous infusions of Sorbilact normalize plasma electrolytes in operated patients with rectal cancer after anterior resection of the rectum in the early postoperative period. Normalization of electrolytes in blood plasma in operated patients is confirmed by the presence in the infusion of Sorbilact ions of potassium, sodium, chloru. Sorbilact infusion is recommended for widespread medical use in cancer patients with rectal cancer after anterior resection of the rectum, especially in the early postoperative period.